Clinical antiarrhythmic effects of amiodarone in patients with resistant paroxysmal tachycardias. Issue 1 (July 1980) - Ward, D E; Camm, A J; Spurrell, R A
Abstract : Oral amiodarone, an iodine-containing antiarrhythmic agent, was administered to 72 patients with recurrent paroxysmal tachycardias. Thirty-nine patients had tachycardias associated with the Wolff-Parkinson-White syndrome, 15 patients had paroxysmal atrial fibrillation unassociated with the Wolff-Parkinson-White syndrome, and 18 patients had ventricular tachycardia. In all patients, the frequency of symptomatic attacks had not been reduced by at least three other antiarrhythmic agents alone or in combination. The response to amiodarone treatment was graded according to the patients' subjective response (total suppression, partial suppression, and no effect). Overall, 57 per cent of patients had total abolition of attacks and another 22 per cent had a partial suppression of attacks. Side effects, the most common of which were photosensitivity and gastrointestinal upsets, occurred in 44 per cent and were sufficiently severe to warrant withdrawal of treatment in 15 per cent. These results confirm that amiodarone is of considerable value in the treatment of recurrent paroxysmal arrhythmias resistant to other drugs.